2014
DOI: 10.1002/cbic.201300577
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Promotes Binding of α‐Conotoxin MII at α3β2 Nicotinic Acetylcholine Receptors

Abstract: α-Conotoxin MII (α-CTxMII) is a 16 amino acid peptide with the sequence GCCSNPVCHLEHSNLC containing disulfide bonds between Cys2-Cys8 and Cys3-Cys16. This peptide, isolated from the venom of the marine cone snail Conus magus, is a potent and selective antagonist of neuronal nicotinic acetylcholine receptors (nAChRs). To evaluate the impact of channel-ligand interactions on ligand binding affinity, homology models of the heteropentameric α3β2-nAChR were constructed. The models were created in MODELLER using cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…A recent report describes the use of a Lys 4 solubilising C-terminus tag to enable the synthesis and Na V subtype selectivity of three previously reported C. consors g-conotoxins, g-CnVIB, g-CnVIC and g-CnVID. 826 Further studies have reported on the structure and activity of dicarba analogues of a-RgIA, 827 the inuence of disulde connectivity on structure and bioactivity of a-TxIA, 828 the inuence of acetylcholine to affect the binding of a-MII at nAChRs, 829 the neuronal target selectivity of the Conus textile T-superfamily peptide TxVC, 830 and the Ca 2+ -activated K + (BK) channel selectivity of the unusual M superfamily conotoxin Vt3.1. 831 11 Tunicates (ascidians)…”
Section: Molluscsmentioning
confidence: 99%
“…A recent report describes the use of a Lys 4 solubilising C-terminus tag to enable the synthesis and Na V subtype selectivity of three previously reported C. consors g-conotoxins, g-CnVIB, g-CnVIC and g-CnVID. 826 Further studies have reported on the structure and activity of dicarba analogues of a-RgIA, 827 the inuence of disulde connectivity on structure and bioactivity of a-TxIA, 828 the inuence of acetylcholine to affect the binding of a-MII at nAChRs, 829 the neuronal target selectivity of the Conus textile T-superfamily peptide TxVC, 830 and the Ca 2+ -activated K + (BK) channel selectivity of the unusual M superfamily conotoxin Vt3.1. 831 11 Tunicates (ascidians)…”
Section: Molluscsmentioning
confidence: 99%
“…It is known to potently and selectively block α3β2‐nAChR isoforms . Due to the importance of nAChRs in the progression of neurodegenerative diseases, libraries of αCTx MII mutants were screened for binding affinity toward the pentameric homology model of the α3β2 isoform of rat neuronal nAChR . This system is reasonably well understood and was selected so that we could focus on evaluating the efficacy of GAMPMS.…”
Section: Methodsmentioning
confidence: 99%
“…The highest binding affinity (the lowest docking energy) score was chosen to explore the binding mode of the docked compound in the GABAAT enzyme using PyRx program. For the analysis of the docking calculations, 9 conformers were considered for each ligand-target complex, and the resulting docking clusters were calculated with a 2.0 Å root mean squared deviation (RMSD) tolerance on the heavy atoms [16]. The 3D molecular interaction models of the complex (involving hydrogen bonding and hydrophobic interactions) were displayed using the pymol visualization software.…”
Section: Molecular Docking's Computational Proceduresmentioning
confidence: 99%